Entrincheiramento na carreira: um estudo numa instituição pública de ensino superior - Rocha, Hérica Kalianny Lopes Figueirêdo (2019)
This study aimed to investigate the relationship between organizational entrenchment and the career of technical-administrative servants of a public higher education institution located in the interior of the Brazilian Northeast. The research, of the type survey, has descriptive and explanatory nature, with quantitative approach. Data were collected from 107 technicians from a federal university located in the city of Mossoró, Rio Grande do Norte. For the purpose of the research, the Carson, Carson and Bedeian (1995) Career Entrenching Scale, was adapted and validated for Brazil by Magalhães (2008). The scale has 12 variables arranged in three dimensions, and each dimension has four assertions. The dimensions are Career Investments, Emotional Costs, and Limitation of Alternatives. The data were treated statistically, using descriptive statistical modules, as well as Factor Analysis and Variance Analysis (ANOVA). The results pointed to a relationship between entrenchment and the career of the servers studied. The "Career Investments" factor prevailed among the other dimensions of the entrenchment, showing that the investments that the administrative technicians made during their career can lead many of these professionals to believe that they invested too much to want to face new challenges. It was also verified that only in the variable "gender" there were significant differences between the means, numbers found through ANOVA, in which it was evidenced that the men tended to fear more the change of career due to the investments made, while the women have stronger affective ties with colleagues, which may be a deterrent to possible career changes. The research contributed theoretically bringing the discussion of entrenchment to the Public Administration, aiming to fill gaps in studies in this area; and also collaborated with organizations in order to make managers better acquainted with their professionals and develop strategies that minimize the impacts of the issue in the workplace and can create instruments to elevate the affective commitment of their employees, which is one of the great challenges of any organization